The Effect of Inflation and Population on Unemployment Rate in North Sumatra Province - Siregar, Henny Mawarta (Economic: Journal Economic and Business, 2023)
Unemployment is an economic problem that still occurs in Indonesia, especially in North Sumatra Province. This research aims to analyze the extent of the relationship between population size and inflation on poverty in North Sumatra Province. The research method used is quantitative with secondary data sources from the Central Statistics Agency for the period 2001 - 2021. The research results show that simultaneously the variables of population and inflation have a significant effect on poverty. Meanwhile, partially, in the long term, population size has a negative and significant effect on the poverty level in North Sumatra Province. In the short term, the inflation variable has a positive effect on unemployment. It is hoped that this research will be useful for the government in making decisions regarding employment issues, especially poverty issues.